Immunohistochemical Evaluation of p53 and Ki-67 Expression in Oral Leukoplakia and Oral Squamous Cell Carcinoma - Abdelghani, Abedalla (Bangladesh Journal of Medical Science, 2026)
Background Oral leukoplakia (OL) is one of the most common oral potentially malignant disorders, with a reported malignant transformation rate of 0.13-17.5%. Oral squamous cell carcinoma (OSCC) accounts for over 90% of oral malignancies. Molecular biomarkers such as p53 and Ki-67 play crucial roles in identifying lesions at higher risk of malignant transformation. Methods A cross-sectional study was conducted on 75 formalinfixed paraffin-embedded tissue blocks (25 OL, 25 OSCC, and 25 NOM). Immunohistochemistry was performed using standard protocols for p53 and Ki-67. The percentage of positively stained cells was calculated and analyzed statistically. Results: p53 expression was significantly higher in OSCC (68.4 ± 12.3%) compared to OL (42.7 ± 15.6%) and NOM (8.3 ± 4.2%) (p < 0.001). Ki-67 expression followed a similar pattern with highest expression in OSCC (54.2 ± 11.8%), intermediate in OL (28.9 ± 10.4%), and lowest in NOM (5.7 ± 3.1%) (p < 0.001). A positive correlation was observed between p53 and Ki-67 expression in both OL (r = 0.58, p = 0.002) and OSCC (r = 0.63, p < 0.001). Dysplastic OL showed significantly higher expression of both markers compared to non-dysplastic OL (p < 0.05). Conclusion The progressive increase in p53 and Ki-67 expression from NOM to OL to OSCC suggests their role in oral carcinogenesis. These markers may help identify OL lesions at higher risk of malignant transformation, potentially improving patient management and outcomes. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S89-S95